2011
DOI: 10.2174/138920111794295819
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Breast Cancer Stem Cell into Breast Somatic Stem Cell

Abstract: Stem cells have an important role in cell biology, allowing tissues to be renewed by freshly created cells throughout their lifetime. The specific micro-environment of stem cells is called stem cell niche; this environment influences the development of stem cells from quiescence through stages of differentiation. Recent advance researches have improved the understanding of the cellular and molecular components of the micro-environment--or niche--that regulates stem cells. We point out an important trend to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…(37) In cancer research, reversing the breast cancer stem cell into breast somatic stem cell has been reported. (38) The reprogramming/reversing could be conducted with a single gene or series of genes modifications. Or simply by changing the microenvironment, as being conducted in stem cell research for differentiating stem cell.…”
Section: Future Research Perspectivementioning
confidence: 99%
“…(37) In cancer research, reversing the breast cancer stem cell into breast somatic stem cell has been reported. (38) The reprogramming/reversing could be conducted with a single gene or series of genes modifications. Or simply by changing the microenvironment, as being conducted in stem cell research for differentiating stem cell.…”
Section: Future Research Perspectivementioning
confidence: 99%
“…For example, proliferation and survival of CD133+ glioma CSCs were shown relied on Hedgehog pathway (Clement, et al, 2007;Ehtesham, et al, 2007) Major signaling pathways in normal stem cells regulating proliferation and differentiation were also shown to be the key player in CSCs. These pathways could be suggested as the target for CSC eradication (Crea, et al, 2011) or CSC reprogram (Wijaya, et al, 2011).…”
Section: Csc In Pgxmentioning
confidence: 99%
“…13 The application of stem cell therapy in the medical field are rapidly developing. Efforts to achieve the applications also vary, such as the development of stem cell and its microenvironment isolation methods 14,15 , development of methods to increase the number of stem cells [16][17][18][19][20][21][22] , the development of stem cell differentiation methods 23 (including cell reprogramming) 24,25 , stem cell storage methods 26,27 , the development of stem cell transplantation methods 16,28 , etc. Since then, some particular stem cell types with their potential differentiation capacities can be isolated and cultured to meet the requirement of each clinical study to be explored.…”
Section: B I O P H a R M A C E U T I C A L I N S T I T U T Ementioning
confidence: 99%